PERFIL ANTROPOMÉTRICO E COMPARAÇÃO DE DIFERENTES MÉTODOS DE AVALIAÇÃO DA COMPOSIÇÃO CORPORAL DE ATLETAS DE FUTSAL MASCULINO - Maitê Martins Fagundes; Camile Boscaini (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
Futsal is a sport that requires good physical fitness becoming essential to the establishment of specific forms of nutritional evaluation. To Compare the body mass index (BMI) and fat percentage (% G) and analyse four protocols that have different calculations for% G. It is a cross-sectional study, consisting of a sample of 17 futsal male athletes. The Anthropometry was the parameter used for assessment of nutritional status, through the IMC and % G. for the estimation of body fat skinfolds were used and applied the calculations. Acceptable average values were found for BMI and ideal for% G. BMI presented the classification of overweight in 50% of the studied in relation to% G we can verify that athletes exhibit ideal rating and healthy. The comparison of BMI with% G noted that for the first anthropometric marker athletes showed higher prevalence of overweight 52.9%, on the other hand% G ideal. We found a significant difference between the protocols regarding body fat (P < 0.001), Jackson (1985) presents significant values lower than the other protocols that do not differ. The IMC is not the most reliable indicator for nutritional classification of athletes, and must be associated with a body composition marker. The protocols of Jackson (1985), Jackson (1978), would not be adequate for athletes of futsal. I Faulkner (1968) and Gh (1985) by not using the folds of lower limbs, feature more realistic results with athletes of this sport.